Dietary melanoidins as emerging functional components: interactions with gut microbiota and implications for nutritional modulation of intestinal health - Chen, Jialiang; Gao, Xiaoyi; Hou, Yue; Liang, Guowei (Frontiers in Nutrition, 2025)
Melanoidins, complex brown polymers formed during the Maillard reaction in thermally processed or fermented foods, are increasingly recognized for their nutritional relevance beyond sensory contributions. Emerging evidence suggests that they may act as prebiotic-like compounds that resist human digestion and undergo microbial fermentation in the colon, producing metabolites such as short-chain fatty acids (SCFAs). These metabolites are proposed to support intestinal barrier function, inflammation, and host metabolism. This review summarizes current knowledge on the gastrointestinal fate, microbial fermentation, and putative bioactivities of dietary melanoidins, with a focus on their interactions with gut microbiota. We compare the structural diversity among food sources and discuss potential health implications. However, most evidence to date derives from in vitro and animal studies, with limited clinical validation. Key challenges remain in classification, extraction, and the translation of preclinical findings into human applications. Addressing these gaps will be essential to establish the nutritional potential of melanoidin-rich foods in personalized and preventive nutrition strategies for gut health. Future studies integrating standardized extraction, structural characterization, and clinical validation are essential to establish the role of dietary melanoidins in personalized nutrition.